Effect of vitamin E on ruminal fermentation in vitro - Naziroglu, M; Güler, T; Yüce, A (Wiley, 2002)
The effects of vitamin E on pH value. total protozoa counts, volatile fatty acid (VFA), ammonia nitrogen and lactate levels were examined using an in vitro ruminal incubation system. The ruminal fluid (100 ml) of the first and second group was supplemented with 0.4 mg or 0.8 mg of vitamin E. respectively. Samples were taken immediately before and following 3, 6, 12 and 24 h of incubation at 39degreesC and analysed for the total protozoa counts, the pH and the levels of ammonia nitrogen, lactate and VFA. Levels of propionate at 24 h and ammonia nitrogen at 12 and 24 h were significantly higher in the second group than in the control. In contrast, the levels of butyrate at 6, 12 and 24 h and lactate at 6, 12 and 24 h were lower in the second group than in the control. Propionate at 24 h, acetate levels at 6, 12 and 24 h and ammonia nitrogen levels at 6, 12 and 24 h and total rumen protozoa counts at 6, 12 and 24 h were significantly higher in the second group as compared with control. In contrary, butyrate levels at 6, 12 and 24 h, lactate levels at 6, 12 and 24 h were lower in second group than in control. There was no statistically significant difference among the groups in the pH values. In conclusion, the addition of vitamin E to in vitro ruminal fluid was found to increase the concentrations of acetate and propionate, total counts of protozoa. levels of ammonia nitrogen, but to decrease the butyrate and lactate levels of the ruminal aliquots in in vitro ruminal fermentation.
Keywords: Alpha-Tocopherol; Rumen; Selenium; Protozoa; Acid